Electromyographic study of the trapezius (middle portion) and rhomboideus major muscles in movements of the trunk - De Freitas, V.; Vitti, M. (My University, 1980)
The authors studied the trapezius (middle portion) and rhomboideus major muscles in movements of flexion, extension, inclination and rotation of the trunk. The electromyographic records demonstrate that such muscles show activity only at the ending of flexion, being inactive in the other movements.
Keywords: electromyography; human cell; movement (physiology); muscle; normal human; rhomboideus major muscle; trapezius muscle; trunk; Back; Electromyography; Human; Male; Movement; Muscles